Pharmaceutical Co-Crystallization: Regulatory Aspects, Design, Characterization, and Applications - Abdul Raheem Thayyil; Thimmasetty Juturu; Shashank Nayak; Shwetha Kamath (Tabriz University of Medical Sciences, 2020)
Pharmaceutical co-crystals are novel class of pharmaceutical substances, which possess an apparent probability of advancement of polished physical properties offering stable and patentable solid forms. These multi-component crystalline forms influence pertinent physicochemical parameters like solubility, dissolution rate, chemical stability, physical stability, etc. which in turn result in the materials with superior properties to those of the free drug. Co-crystallization is a process by which the molecular interactions can be altered to optimize the drug properties. Co-crystals comprise a multicomponent system of active pharmaceutical ingredient (API) with a stoichiometric amount of a pharmaceutically acceptable coformer incorporated in the crystal lattice. By manufacturing pharmaceutical co-crystals, the physicochemical properties of a drug can be improved thus multicomponent crystalline materials have received renewed interest in the current scenario due to the easy administration in the pharmaceutical industry. There is an immense amount of literature available on co-crystals. However, there is a lack of an exhaustive review on a selection of coformers and regulations on co-crystals. The review has made an attempt to bridge this gap. The review also describes the methods used to prepare co-crystals with their characterization. Brief description on the pharmaceutical applications of co-crystals has also been incorporated here. Efforts are made to include reported works on co-crystals, which further help to understand the concept of co-crystals in depth.